Significance of haemorrhagic lacunes on MRI in patients with hypertensive cerebrovascular disease and intracerebral haemorrhage - Scharf, Johann; Bräuherr, E.; Forsting, Michael; Sartor, Klaus (Neuroradiology, 1994)
Our purpose was to determine the frequency and signifcance of haemorrhagic lacunes (HL) on MRI in patients with a history of, or at risk for intracerebral haemorrhage. We examined 72 patients with old spontaneous intracerebral haemorrhage (ICH) using T1-and T2-weighted spin-echo sequences. MRI studies of 137 consecutive patients with cerebrovascular disease but no known ICH were also reviewed. Both groups showed about the same degree of age-related white matter change and nonhaemorrhagic lacunar infarcts, whereas the ICH group had a higher frequency of HL (12/72 patients) than the non-ICH group (6/131 patients,p<0.01). These results correlate well with reported pathological findings. We conclude that haemorrhagic lacunes found on MRI studies of patients with cerebrovascular disease may suggest a higher risk of intracerebral haemorrhage.